62. ANGIOMATOID FIBROUS HISTIOCYTOMA WITH LOCOREGIONAL LYMPH NODE METASTASIS: A CASE REPORT. (February 2015) - Young, Kathleen; Robbins, Elizabeth; Harvey, Theresa; Bonar, Fiona; Mahar, Annabelle; Thompson, John
Abstract : Angiomatoid fibrous histiocytoma is a rare mesenchymal neoplasm of intermediate malignant potential which occurs predominantly in the extremities of children and young adults. Local recurrence occurs in 2–12% of cases. The rate of local metastasis, defined as a second nodule in the same extremity or within loco regional lymph nodes, ranges from 1–5%, and is related to the depth of invasion, presence of infiltrative margins, and anatomical site. The average time between surgery and local metastasis is 1–2 years. Distant metastasis has been reported but is rare. We present a case of a 24 year old male who presented with a mass in his right forearm. An initial biopsy and subsequent wide excision of a red-brown mass, confined to the dermis and subcutis, was submitted. Histology showed typical features of an angiomatoid fibrous histiocytoma including solid sheets of histiocytoid and spindle cells, areas of haemorrhage and cystic change, a prominent lymphoid component at the periphery, and a fibrous pseudocapsule. Immunohistochemical staining for desmin, CD99, and CD68 were positive. FISH studies showed positive EWSR1 (22q12) rearrangement. Despite complete excision and the tumour's superficial location, the patient represented with local metastasis to the right epitrochlear lymph node and three right axillary lymph nodes five months after initial surgery. Angiomatoid fibrous histiocytoma shows three characteristic translocations that it shares with several other tumours that appear and behave quite differently. EWSR1-CREB1 is the most frequent gene fusion identified. EWSR1-ATF1 and FUS-ATF1 rearrangements are also described. The type of gene fusion does not appear to correlate with clinical behaviour, nor does the presence of pleomorphism. Evaluation for the characteristic translocations should always be interpreted in conjunction with morphologic features and tumour immunoprofile to avoid misdiagnosis of this rare tumour.